DISTANCE EDUCATION AND SOCIAL MEDIA LEARNING: UNDERGRADUATE PERCEPTIONS - Zainal Fikri Zamzuri; Syamsul Ariffin Yahaya; Azlan Abdul Aziz (Journal of Islamic, Social, Economics and Development, 2022)
The proliferation of social media in todays’ setting has also permeated into the education realm. Social media technology on various platforms has presented another alternative tool for adult learners to learn and improve in their studies. The fast technological advancement and expansion have allowed educational practitioners, instructors, trainers, and learners to utilize the multitude of technology-supported learning tools to ease the teaching and learning process. These social media platforms have been touted to have huge benefits and potential for adult learning in the distance education environment. However, to understand the benefits, this study intends to shed some light on how adult learners perceive social media platforms and their potential use in the learning process and outcomes. Little is known about their social media knowledge and expertise, or their interest in using these platforms for learning, collaboration, and interaction. The available technology does not ensure success unless it is properly designed and implemented. It is to avoid the risk of being technologically driven and not pedagogically driven as it is supposed to be. The result indicates that the adult learners are very much open to the various social media platforms but they are inclined towards the more accustomed ones and not without proper considerations.